Antara Otoritas Tradisi dan Tuntutan Modernitas - Atika Ilmah Mrp; Khairunisa Azzahra; Mahmud Simamora; Farid Adnir (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2026)
The evolution of modern society demands an interpretation of the Qur’an capable of addressing various contemporary issues. Consequently, modern exegesis adopts a rational, contextual, and interdisciplinary approach to understanding the verses of the Qur’an. This article aims to explain the concept of modern exegesis, examine critiques from both traditionalist and modernist circles, and analyze the methodological challenges present in modern exegesis. This study employs a literature review method with a descriptive-analytical approach through the examination of various books, journal articles, and relevant scholarly sources. The results indicate that modern exegesis plays a crucial role in maintaining the relevance of the Qur’an’s teachings amidst changing times, yet it also faces criticism for being perceived as overly emphasizing rationality and risking a departure from classical exegetical methodology. Conversely, modernists argue that the traditional approach is insufficiently responsive to contemporary issues. Furthermore, modern exegesis faces various methodological challenges, such as the use of hermeneutics, the subjectivity of exegetes, and the debate between textual and contextual approaches. This article provides a more comprehensive understanding of the critiques and methodological issues in modern exegesis, and emphasizes the importance of combining innovative approaches to exegesis with the fundamental principles of classical exegesis so that Qur’anic studies remain relevant and grounded in a strong scientific foundation. Therefore, a balance is needed between the renewal of exegetical methods and the preservation of the fundamental principles of classical exegesis.